Quantitative computerized color vision testing in diabetic retinopathy: A possible screening tool? - Rashid Al Saeidi; Marcus Kernt; Thomas C Kreutzer; Guenther Rudolph; Aljoscha S Neubauer; Christos Haritoglou (Oman Journal of Ophthalmology, 2013)
Purpose: To evaluate the efficacy of a computerized color vision testing (Arden color contrast test) as a screening test for detection of diabetic macular edema (DME). Materials and Methods: A consecutive, prospective case series of 83 eyes of 42 diabetic patients with and without macular edema was enrolled. Macular edema was assessed clinically by stereoscopic grading and by central retinal thickness measurement with optical coherence tomography (OCT). Additionally, a computerized chromatest for the protan- and tritan-axis was performed. Analysis of test characteristics included receiver operating characteristic (ROC) curves and calculated sensitivity and specificity. Results: Sixty-one eyes had clinically significant macular edema (CSME). OCT yielded an area under the ROC curve (AUC) of 0.92. Color vision testing yielded an AUC of 0.82 for the tritan- and 0.80 for the protan-axis. Using a cut off of 199 microns OCT resulted in a 100% sensitivity at 39% specificity. With a cut-off of 4.85, color testing yielded a sensitivity of 100% at a specificity of 8% on the tritan-axis, respectively. Considering OCT instead of clinical examination as a reference standard resulted in a comparable high sensitivity, but low specificity for color vision testing. Disturbance of the tritan axis was more pronounced than for the protan axis in present macular edema and also better correlated (r = 0.46) with retinal thickness measured with OCT. Conclusions: Computerized, quantitative color testing using the chromatest allows detection of diabetic maculopathy with high sensitivity. However, only a low specificity exists for retinal macular edema, as in diabetic retinopathy (DR) frequently abnormalities of the tritan axis exist before any retinal thickening occurs.